Experimental and finite element analysis of modular prefabricated composite beam-column interior joints. (November 2021) - Wu, Chenglong; Zhou, Yang; Liu, Jiming; Mou, Ben; Shi, Jiyuan
Abstract: This contribution presents quasi-static tests of three modular prefabricated composite beam-column interior joints (MPCIJs), analyzing the strain distribution, ductility, energy consumption, strength, and stiffness degradation. Three finite element models were established by ABAQUS and compared with quasi-static test results to verify their correctness. The stress mechanism of different materials in MPCIJs was further analyzed. Results showed that the absolute value of the plastic drift ratio was 6.41–8.01% rad, the ductility coefficient was 3.50–4.50, and the equivalent viscous damping coefficient was 0.32–0.33. The overall degradation performance of MPCIJs strength and stiffness were relatively stable. MPCIJs achieved good seismic performance and large rotational deformation capacity. The stress (strain) in the joint module, consistent with the 'diagonal compression bar', was diagonally distributed. The high-stress connection bolt at the column end is located on both sides of the centerline along the direction of the beam length. The internal stress of concrete follows an antisymmetric distribution along the diagonal direction and diffuses outward at an angle of 45°. Highlights: A new type of modular composite joint is proposed. Physical tests and finite element analysis of composite joints are carried out. Verify the correctness of the modular composite joint finite element model. The stress mechanism of joints with different composition materials is clarified. The modular composite joint meets the requirements of seismic fortification.